Management of pericarditis in bovines through pericardiocentesis - Bharti, Brihaspati (Indian Journal of Veterinary Surgery, 2025)
The study included seven clinical cases bovines with traumatic pericarditis. A thorough physical, clinical and ultrasound examinations were performed. All the animals were presented with the history of variable duration of brisket oedema and anorexia. Auscultation of heart revealed muffled, splashing and frictional sounds. Under local infiltration analgesia, pericardiocentesis was performed by using 16-G spinal needle through a puncture at the level of 5th intercostal space just dorsal to the elbow, and the pericardial fluid was drained and lavaged. The pericardial fluid was purulent and its volume was e”1 L in the 1st or subsequent pericardiocentesis in all cases. Brisket oedema decreased in four cases and the appetite restored partially in three cases and completely in two cases the pericardiocentesis procedure. The survival period of animals after pericardiocentesis ranged from 5 days to 9 weeks. It can be concluded that pericardiocentesis can be used as an emergency procedure for the management of traumatic pericarditis in bovines even under field conditions.